Is There a Cumulative Effect for Congenital Heart Defects in Monochorionic Twins after Assisted Reproduction? – A Retrospective Analysis at a Tertiary Referral Center - Zdanowicz, Jarmila A.; Yildrim, Gülay; Fonseca, Andreia; Hecher, Kurt; Tavares de Sousa, Manuela (Geburtshilfe und Frauenheilkunde, 2024)
The aim of our study was to compare maternal, chorionicity and neonatal complications in monochorionic (MC) twins between spontaneously conceived (SC) and assisted reproductive technologies (ART) pregnancies.This was a retrospective cohort study between January 2010 to December 2019 at a tertiary referral University center. All consecutive pregnancies with MC twins that delivered at our University hospital were included. Maternal, chorionicity and neonatal complications were recorded and compared between SC and ART pregnancies.393 MC pregnancies were included for final analysis, including 353 (89.8%) SC and 40 (10.2%) pregnancies conceived after ART. Hypothyroidism was the only maternal condition seen significantly more often in ART pregnancies (35.0% vs 12.5%, p = 0.001). There were no significant differences in chorionicity complications, such as twin-twin transfusion syndrome, selective fetal growth restriction and twin anemia-polycythemia sequence (40.0% in ART pregnancies vs 31.6% in SC pregnancies, p = 0.291). At least one congenital anomaly in one twin was seen significantly more often in ART pregnancies (18.8% vs 8.1%, p = 0.004), especially congenital heart defects (16.3% vs 6.2%, p = 0.005). There were no other significant differences in neonatal outcomes between both groups, however, there were non-significant trends in gestational age at delivery (34 weeks in ART pregnancies vs 35 weeks, p = 0.078) and birthweight (1951 g ± 747 in ART pregnancies vs 2143 g ± 579, p = 0.066).This is the largest cohort study to date comparing maternal, chorionicity and neonatal complications between MC twin pregnancies after ART and after SC. Hypothyroidism was the only maternal condition occurring more frequently in pregnancies conceived after ART. There were no significant differences in chorionicity complications, in contrast to previously reported studies. While MC twins and ART pregnancies per se are known to be at risk for congenital heart defects, there seems to be a cumulative effect in MC pregnancies conceived after ART.
Keywords: assisted reproductive technologies; congenital heart defect; congenital anomalies; monochorionic twins; sFGR; TAPS; TTTS